Workshop of Human Resource Capacity Development Through Canva Training to Increase Msmes Digital Promotion in Bengkalis: (Case Study On Marketing Aspect) - Salbi, Salbiyah; Hutomo Atman Maulana (Jurnal Pemimpin Bisnis Inovatif, 2024)
This seminar is an activity carried out to assist students and the wider community in developing theability of human resources to build creative businesses by utilising the Canva application. Increased digitalpromotion is key for Micro, Small and Medium Enterprises (MSMEs) to increase their visibility andcompetitiveness. This workshop aims to develop the capacity of human resources in Bengkalis Regency throughtraining using the Canva platform. Canva is an easy-to-use online graphic design tool, and this workshop isdesigned to provide an in-depth understanding of using Canva in the context of digital promotion. Participantswill be guided to understand the basic concepts of graphic design, digital promotion strategies, and theapplication of skills using Canva. During the training, participants will engage in hands-on practical sessions tocreate attractive and effective digital promotional materials for their MSMEs. Keywords: Workshop, Digital Promotion, Canva Training, MSMEs in Bengkalis.